Cultural robotics : first International Workshop, CR 2015, held as part of IEEE RO-MAN 2015, Kobe, Japan, August 31, 2015. Revised selected papers /: first International Workshop, CR 2015, held as part of IEEE RO-MAN 2015, Kobe, Japan, August 31, 2015. Revised selected papers. (2016) - Unknown
No abstract available